1D AND 2D NMR STUDIES OF 2â??(2â??(BENZYLOXY)â??3â??METHOXYPHENYL)â??1Hâ??BENZIMIDAZOLE - , Mohammed Hadi Alâ??Douh, Shafida Abd Hamid and Hasnah Osman ([Yogyakarta] : Fak. MIPA Universitas Gadjah Mada, 2007)
The reaction of Benzyl o&ndash